Un projet d’alliance entre Kilwa et la France contre l’expansionnisme omanais, étude d’une lettre en arabe de mfalme Sulaymān b. Ḥasan à Louis XVIII - Abdelhakim Belhacel; Fu’ad Al-Qaisi (Afriques)
The « Réunion » series of the Archives nationales d’outre-mer holds correspondence between the French and the Muslim rulers of East Africa. One of these letters, written in 1819, had not previously been translated. Its study sheds crucial light on the nature of relations between Swahili, Omani and French at the beginning of the 19th century. It shows the importance of slave-trading networks for French diplomacy and how they persisted after the official abolition of the slave trade. It also explains how the Sultanate of Kilwa attempted to break away from Omani control. It also shows the importance of using Arabic for diplomatic correspondence in the Indian Ocean. The letter from mfalme Sulaymān b. Ḥasan to Louis XVIII aimed to seal an alliance between France and the Sultanate of Kilwa against the Omanis settled in Zanzibar, thanks to the good offices of an Arabic-speaking scholar and a slave trader. The study of this document includes a reproduction and an analysis of the letter and its envelope, a transcription, a translation and an analysis to understand the context (actors, political situation) and to identify its contribution to our knowledge of the strategies of resistance of the Swahili sovereigns in the face of Omani expansionism in East Africa.